Non‐traditional elements of the technology of agricultural crop cultivation using fertilizers‐ameliorants - A. S. Mezhevova; A. I. Belyaev (Юг России: экология, развитие)
Aim. The aim of research is to determine the suitability and fertilizing value of fertilizers‐ameliorant, as well as to assess the degree of their contamination with heavy metals; approbation of fertilizers‐ameliorants in various conditions in the cultivation of agricultural crops.Material and Methodology. The main agrochemical parameters of sewage sludge and the chemical composition of glauconite were studied by analytical methods in laboratory conditions. The content of heavy metal cations in the sewage sludge was determined by atomic absorption spectrometry. The object of research in the first experiment is seed potatoes (variety Arosa); in the second experiment – safflower (variety Alexandrite).Results. Studies of the physico‐chemical parameters of the processed sewage sludge have been carried out. It has been established that the composition of the sediment is an effective organic fertilizer. The content of heavy metals in sewage sludge does not exceed the maximum allowable concentrations.   It   has   been   determined   that  silica   is   the   basis   of glauconite, and it also contains phosphorus, potassium and magnesium fertilizers. It has been proven that the use of sewage sludge as an independent  fertilizer,  as  well  as  in  combination  with  glauconite,  has significantly increased the yield of seed potatoes and safflower.Conclusion. The use of non‐traditional ameliorant fertilizers is advisable along with the use of classical mineral fertilizers, as they allow increasing the  yield  of  some  agricultural  crops,  as  well  as  achieving  savings  in irrigation water.